ChemInform Abstract: Synthesis of Brominated Novel N‐Heterocycles: New Scaffolds for Antimicrobial Discovery. Issue 20 (April 2016) - Biswas, Nripendra Nath; Kutty, Samuel K.; Iskander, George M.; Mielczarek, Marcin; Bhadbhade, Mohan M.; Gardner, Christopher R.; Black, David StC.; Kumar, Naresh
Abstract: Novel brominated N‐heterocycles based on aminobromopyrrolone and bromopyridazinone scaffolds are prepared from brominated furanones by reaction with hydrazines.